2020
DOI: 10.1093/tas/txaa151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medium-chain fatty acids as alternatives to ZnO or antibiotics in nursery pig diets

Abstract: The objective of this experiment was to evaluate the effects of medium chain fatty acids (MCFA) on nursery pig performance in place of ZnO and carbadox. In this trial, 360 weanling pigs (DNA 200 x 400; 5.4 ± 0.07 kg BW) were fed for 35 days, with 6 pigs/pen and 10 replicate pens/treatment. Upon weaning, pigs were weighed and allotted to pens based on BW in a completely randomized design to one of 6 treatment diets: 1) Negative control (no added ZnO or carbadox); 2) Control + 3,000 ppm ZnO in phase 1 and 2,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…In contrast, only a 2.8% increase in ADLG was recorded with 2% MCOA in feed (Mohana Devi and Kim, 2014). Furthermore, Dahmer et al (2020) found that a blend of C6:0, C8:0 and C10:0 did not significantly affect performance compared to a negative control diet, whereas ZnO (3,000 mg/kg) improved ADLG (P<0.001) but the inclusion level of MCOA was not specified. The size of response was likely influenced by the type and dose rate of MCOA and pathogen challenge.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, only a 2.8% increase in ADLG was recorded with 2% MCOA in feed (Mohana Devi and Kim, 2014). Furthermore, Dahmer et al (2020) found that a blend of C6:0, C8:0 and C10:0 did not significantly affect performance compared to a negative control diet, whereas ZnO (3,000 mg/kg) improved ADLG (P<0.001) but the inclusion level of MCOA was not specified. The size of response was likely influenced by the type and dose rate of MCOA and pathogen challenge.…”
Section: Discussionmentioning
confidence: 87%
“…MCFAs undergo esterification with glycerol to form triglycerides, known as medium-chain fatty acid triglycerides (MCTs). In addition to being a source of energy, MCFAs can also improve intestinal morphological structure and growth, prevent infection, regulate immunity, and act as an alternative to antibiotics (6,7). Both MCFAs and MCTs exhibit strong bacteriostatic activity against a variety of pathogens, including gram-positive and gram-negative bacteria, viruses, fungi, algae, and protozoa (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Medium-chain fatty acids (MCFA) with 6 to 12 carbon atoms, including caproic (C6), caprylic (C8), capric (C10), and lauric (C12) acids. MCFA can be absorbed directly into the portal blood and may contribute to immediate energy for the enterocytes [ 7 , 8 ]. Moreover, MCFA possess antibacterial effects and may thereby reduce the amount of viral and bacterial pathogens in the feed and the risk of disease transmission [ 9 ].…”
Section: Introductionmentioning
confidence: 99%